The Effectiveness of Cognitive Behavioral Counseling with Cognitive Restructuring Techniques in Reducing Bullying Behavior Tendencies among Grade X Hospitality Students in Vocational High Schools - Johni Hotlan Saragih; Nyoman Dantes; Putu Ari Dharmayanti (Bisma The Journal of Counseling, 2025)
This study is motivated by the increasing prevalence of bullying behavior in school environments, which has negative impacts on students’ psychological well-being and academic achievement. Therefore, strategic efforts through appropriate counseling services are needed. This study aims to analyze the effectiveness of the Cognitive Behavioral counseling approach using the Cognitive Restructuring technique in reducing tendencies toward bullying behavior among Grade X Hospitality students at a Vocational High School. This study employed a quantitative approach with a one-group pretest–posttest design. The research subjects were Grade X Hospitality students at the vocational high school, with a total of eight students participating in the trial. Data were collected through questionnaires and documentation. The instrument used was a bullying behavior tendency scale. The data analysis technique applied in this experimental study was a t-test. The results showed that the Asymp. Sig. (2-tailed) value was 0.005 < 0.05, indicating a significant difference between pretest and posttest scores. Thus, the Cognitive Behavioral counseling approach with the Cognitive Restructuring technique is effective in reducing students’ tendencies toward bullying behavior. This study has implications for providing practical guidance for guidance and counseling practitioners in schools.